2008
DOI: 10.1097/qai.0b013e31816fdc77
|View full text |Cite
|
Sign up to set email alerts
|

Host CCL3L1 Gene Copy Number in Relation to HIV-1-Specific CD4+ and CD8+ T-Cell Responses and Viral Load in South African Women

Abstract: Summary HIV-specific T-cell responses play an important role in control of infection. Because CCL3 has immune modulatory and antiviral activities, we hypothesized that host CCL3 genotype (CCL3L1 gene duplications) would influence the development of effective HIV-specific immune responses. Copy numbers of CCL3L1 were determined for 71 HIV-infected women, and HIV-specific CD4+ and CD8+ T-cell responses to overlapping peptide pools spanning the HIV-1 subtype C genome were simultaneously measured by an interferon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…We have previously shown in a subset of this cohort, that the co-occurrence of gag-specific CD4 T-cell responses with CD8 T-cell responses are a robust marker of good immune integrity and viral control [14]. In keeping with these findings, viral loads were significantly lower (P=0.005) in women with both CD4 and CD8 T-cell responses to Gag compared to those with only CD8 T-cell responses to Gag (Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…We have previously shown in a subset of this cohort, that the co-occurrence of gag-specific CD4 T-cell responses with CD8 T-cell responses are a robust marker of good immune integrity and viral control [14]. In keeping with these findings, viral loads were significantly lower (P=0.005) in women with both CD4 and CD8 T-cell responses to Gag compared to those with only CD8 T-cell responses to Gag (Fig.…”
Section: Resultssupporting
confidence: 78%
“…to both Reg and Env) and responses of higher magnitude had the strongest association with better control of HIV-1 infection. Although magnitudes of CD4 and CD8 T-cell responses to Gag correlated significantly with viral load (not CD4 T-cell counts) as shown previously [14], representation or magnitude of either of these responses were not responsible for why NK responders had better control of infection than NK non-responders. However, when looking at individuals with CD4-supported CD8 T-cell response to Gag (who had lower viral loads) compared to CD8 T-cell responses to Gag alone, these individuals had higher magnitude CD3-negative cell responses to Env (but not Reg).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Notably, CCL3L genes (CCL3L-1, -2, and -3) are subject to copy number variation (reviewed in [30,118]), with higher copies associating with increased CCL3L1 expression [59,119], and enhanced HIV-specific T cell responses [120]. These in vitro biological data along with the in vivo observations demonstrating a strong association between higher CCR5 ligand expression and reduced HIV-AIDS susceptibility, led investigators to determine the associations of the CCL3L1 -containing segmental duplications with HIV-AIDS susceptibility.…”
Section: Mendelian Randomization and Hiv-associated Outcomes: Case Stmentioning
confidence: 99%
“…They found that the CCL3L1-CCR5 genetic risk status and viral load were independent predictors of cCD4 as well as the rate of AIDS progression, and they concluded that the CCL3L1-CCR5 genetic risk status influenced cell-mediated immunity in in- dividuals, which was in part dependent on viral entry-independent mechanisms. Shalekoff et al (2008) reported that individuals with higher CCL3L1 copy numbers have greater CD4+ and CD8+ T-cell responses to the HIV-1 gag protein.…”
Section: Hiv-1 Entry-independent Effect By the Interaction Between CCmentioning
confidence: 99%